System Thinking Approach to Increase Eco-Friendly Maize Production to Support Food Security - Rahmawati, Ulfa Emi; Suryani, Erma; Riski, Raulia (Institut Teknologi Sepuluh Nopember, 2020)
Food security is a high-priority issue for sustainable global agricultural development both quantitatively and qualitatively. Maize is one of the most important food crops in the world after rice and wheat. The biggest contribution of maize production in Indonesia comes from East Java Province, which is 25,60%. Maize production is changing due to increased consumer demand, increased input costs, concerns about food security, and environmental impacts. Climate conditions of marginal land areas (drought) and the use of chemical fertilizers continuously have negative impacts on the amount of production, food security, and soil quality (environment). This situation is dangerous because it will affect the income from farming. Based on these problems, in this study, a system dynamics prospective study will be conducted to develop a conceptual model (Causal Loop Diagram) to increase eco-friendly maize production to support food security. The results of the study are conceptual models that have some important information regarding internal and external factors that affect the productivity and production of eco-friendly maize. The conceptual model produced can be used by the government and stakeholders for decision-making in developing strategies and policies related to eco-friendly maize cultivation systems to support food security. Further research can be done by developing several scenarios to predict the state of the maize farming system in the future.